In Vitro Analysis of Anti-Inflammatory Effects of Purple Chrysanthemum (Chrysanthemum morifolium) Leaf Extract - Nastiti, Gemi; Fatimawali, Fatimawali; Budiarso, Fona Dwiana Hermina; Manampiring, Aaltje Ellen; Kepel, Billy Johnson; Bodhi, Widdhi (Graha Primera Saintifika, 2025)
Chronic inflammatory diseases are the most significant cause of death in the world and pose the greatest threat to human health. Treatment of inflammation is usually done by taking anti-inflammatory drugs that have dangerous side effects in long-term use. Chrysanthemum is the largest horticultural commodity in North Sulawesi that also holds great potential in the world of health. Based on its phytochemical content, purple chrysanthemum leaves have potential as an anti-inflammatory agent. This study aimed to analyze the anti-inflammatory activity of ethanol extract of purple chrysanthemum leaves using the red blood cell membrane stabilization method. This study used an in vitro laboratory experimental method using rat blood. The anti-inflammatory activity of the extract was tested using the red blood cell membrane stabilization method at 4 concentration series, namely 50 ppm, 100 ppm, 200 ppm, and 400 ppm, then measured on a UV-Vis spectrophotometer. The results of phytochemical screening showed that the ethanol extract of purple chrysanthemum (Chrysanthemum morifolium) leaves contains active compounds such as flavonoids, alkaloids, tannins, steroids, and phenolics. The ethanol extract of purple chrysanthemum leaves exhibits anti-inflammatory activity, with higher extract concentrations demonstrating stronger anti-inflammatory effects. The stability percentage values obtained at 50, 100, 200, and 400 ppm were 28.87%, 41.85%, 47.41%, and 64.15% with an IC50 of 235.88 ppm and a correlation coefficient of 0.94.